Laryngeal Squamous Cell Carcinoma in a Mangalarga Marchador Horse - Lang, André; Cobucci, Gustavo; Ibrahim Miranda Antunes, Beatriz; de Oliveira Palermo, Felipe; de Souza Sampaio, Isabella; Cunha Lacreta Junior, Antonio Carlos (Acta Scientiae Veterinariae, 2024)
Background: Squamous cell carcinoma (SCC) is the second most frequent malignant tumor in horses and the major tumor of the upper respiratory or gastrointestinal tract. Most common locations in horses are the periorbital region, external genitalia, urogenital tract, oesophagus, stomach, head and neck especially over mucocutaneous junctions where the skin is not pigmented. The presentation of the disease located in the larynx is rare and clinical signs include dyspnea, respiratory snores, cough, nasal exudate, dysphagia, nasal reflux, weight loss and sore throat. This study aims to report a case of occurrence of laryngeal SCC diagnosed by laryngoscopy and histopathological evaluation. Case: A 14-year-old mangalarga-marchador dark bay colored horse gelding was treated in the municipality of Prados, state of Minas Gerais, Brazil. The physical examination revealed tachycardia, dyspnea and tachypnea, pale oral mucosa, apathy and dysphagia, mucous bilateral nasal secretion with food particles, respiratory noises with inspiratory snoring and increased dyspnea and cough at exercise. At endoscopic examination, a small amount of food material was observed in the nasal cavity, a large tumor was localized in the laryngeal region, with a nodular aspect and an irregular surface, several reddish focal areas and small diffuse bloody ulcerations, extending over the entire surface of the epiglottis and caudally to the arytenoid cartilages, asymmetrically with predominance in the left arytenoepiglottic fold and left arytenoid cartilage. Partial obstruction of approximately 80% of the lumen and left laryngeal hemiplegia was diagnosed. Histopathological examination showed malignant neoplasm diffusely invading the sampled tissue, characterized by "islands" of epithelial cells with large, pleomorphic nuclei and exuberant multiple nucleoli and the presence of numerous mitotic figures, formation of horny pearls and fibrous stroma. Due to the poor prognosis the horse was euthanized. Discussion: The diagnosis of tumors has increased due to the dissemination of information and the care taken by specialized veterinarians. This fact is especially relevant when there is a need for diagnostic tools and expertise as the endoscopy and histopathology. The SCC is a tumor that occurs more frequently in areas with thinning hair and lack of pigmentation of the skin, whether on the head, especially around the nostrils, rostral portion of the face and periocular region, on the external vulvar or preputial genitalia and on the penis itself. Ultraviolet radiation can damage DNA, triggering cellular mutation. As the region of the larynx is well protected from solar radiation, other factors are necessary to induce neoplastic proliferation. Humans, as passive smokers, may develop the disease and horses in constantly smoky environments could be predisposed. Other factors like advanced age, family history of skin cancer and random individual genetic mutations must be considered. Equine papillomavirus type 2 belongs to the family of papillomavirus, which are host specific and have a pronounced tropism for cutaneous and mucosal keratinocytes and is implicated as a causal agent of SCC. The endoscopic examination proved to be essential for the diagnosis of this laryngeal SCC, allowing the macroscopic characterization, with estimation of severity due to airway obstruction, and biopsy for its histopathological conclusion. Despite the possibility of local infiltrative treatments associated with assisted surgical resection, the severity of the tumor was the basis for the decision for euthanasia. Keywords: endoscopy, laringoscopy, tumors, image diagnosis.